Risk factors for long-bone fractures in children up to 5 years of age: a nested case–control study - Baker, Ruth; Orton, Elizabeth; Tata, Laila J.; Kendrick, Denise (BMJ, 2015)
Aim: To investigate risk factors for first long-bone fractures in children up to 5 years old in order to provide evidence about which families could benefit from injury prevention interventions. Methods: Population-based matched nested case–control study using The Health Improvement Network, a UK primary care research database, 1988–2004. Maternal, household and child risk factors for injury were assessed among 2456 children with long-bone fractures (cases). 23 661controls were matched to cases on general practice. Adjusted ORs and 95% CIs were estimated using conditional logistic regression. Results: Fractures of long-bones were independently associated with younger maternal age and higher birth order, with children who were the fourth-born in the family, or later, having a threefold greater odds of fracture compared to first-born children (adjusted OR 3.12, 95% CI 2.08 to 4.68). Children over the age of 1 year had a fourfold (13–24 months, adjusted OR 4.09 95% CI 3.51 to 4.76) to fivefold (37+ months, adjusted OR 4.88 95% CI 4.21 to 5.66) increase in the odds of a long-bone fracture compared to children aged 0–12 months. Children in families with a history of maternal alcohol misuse had a raised odds of long-bone fracture (adjusted OR 2.33, 95% CI 1.13 to 4.82) compared to those with no documented history. Conclusions: Risk factors for long-bone fractures in children less than 5 years old included age above 1 year, increasing birth order, younger maternal age and maternal alcohol misuse. These risk factors should be used to prioritise families and communities for injury prevention interventions.